2001
DOI: 10.1007/s002670010179
|View full text |Cite
|
Sign up to set email alerts
|

Golf Course Development in a Major Tourist Destination: Implications for Planning and Management

Abstract: The planning and design of golf course developments is influenced by many factors. This paper focuses on the environmental ramifications of insufficient or lack of compliance with standard environmental and economic planning practices. Specifically, it looks at a tourist destination location that was under the influence of extensive land development and investment speculation. The Gold Coast in Australia was the focal point for large overseas investment due to changes in government legislation regarding foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Design of sports facilities play an important role in determining successful use (Puhalla, Krans, & Goatley, 1999) while informal spaces are more frequently serving as places for sport (Kural, 2010). Thus for sport tourism generally 'the tangible and intangible characteristics of the sporting resources' acknowledges accessibility, design and maintenance of the physical resources (Shmanske, 1999;Warnken, Thompson, & Zakus, 2001) as well as the surrounding landscape and climate. Sports which rely on the natural environment (for example skiing or scuba diving) may need to consider how maintenance and protection can control resource quality and maintain an appealing atmosphere conducive to participation.…”
Section: Discussionmentioning
confidence: 99%
“…Design of sports facilities play an important role in determining successful use (Puhalla, Krans, & Goatley, 1999) while informal spaces are more frequently serving as places for sport (Kural, 2010). Thus for sport tourism generally 'the tangible and intangible characteristics of the sporting resources' acknowledges accessibility, design and maintenance of the physical resources (Shmanske, 1999;Warnken, Thompson, & Zakus, 2001) as well as the surrounding landscape and climate. Sports which rely on the natural environment (for example skiing or scuba diving) may need to consider how maintenance and protection can control resource quality and maintain an appealing atmosphere conducive to participation.…”
Section: Discussionmentioning
confidence: 99%
“…This can result in water shortages and degradation of water supplies, as well as generating a greater volume of wastewater, particularly, where water-consuming facilities have been established (i.e., golf courses). Golf course maintenance can deplete fresh water resources (Warnken et al, 2001). In recent years golf tourism has increased in popularity and the number of golf courses has grown rapidly, including PR, where there are already 20 golf courses.…”
Section: The Globalized Tourism Industry: Is the Enemy Within?mentioning
confidence: 99%
“…Morzillo and Schwartz (2011) suggested that "hotspots" for rodent control behavior were associated with particular land uses, e.g., low density development such as golf courses, thought to contain more tree cover and luscious vegetation that may attract wildlife than surrounding areas. For example, golf courses contain features, e.g., trees, water, associated with positive outcomes for wildlife (Warnken et al 2001), although use by wildlife varies by species and landscape context (e.g., White andMain 2005, Jones et al 2005). In Bakersfield, impervious surface was the dominant land cover class in some parts of the study area (up to 100% in some 30 m by 30 m blocks), particularly in the east toward the city center, and in the industrial north and south (Fig.…”
Section: Presence Of Species Affected (mentioning
confidence: 99%